2021
DOI: 10.1136/bmjspcare-2021-003036
|View full text |Cite
|
Sign up to set email alerts
|

Primary-level palliative care national capacity: Pallium Canada

Abstract: The need to improve access to palliative care across many settings of care for patients with cancer and non-cancer illnesses is recognised. This requires primary-level palliative care capacity, but many healthcare professionals lack core competencies in this area. Pallium Canada, a non-profit organisation, has been building primary-level palliative care at a national level since 2000, largely through its Learning Essential Approaches to Palliative Care (LEAP) education programme and its compassionate communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…In-depth descriptions of the course’s goals and learning objectives, design, and curriculum development have been published previously. 4 , 37 , 38 …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In-depth descriptions of the course’s goals and learning objectives, design, and curriculum development have been published previously. 4 , 37 , 38 …”
Section: Methodsmentioning
confidence: 99%
“…In-depth descriptions of the course's goals and learning objectives, design, and curriculum development have been published previously. 4,37,38 Learners are asked at the end of the last session of the course to identify three to four things that they will do differently because of participating in the course. These are referred to as the post-course commitment statements.…”
Section: Setting and Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is growing consensus among health care clinicians and researchers that palliative care should be integrated earlier in the serious illness trajectory (1)(2)(3) and that this can be facilitated by generalist clinicians providing primary palliative care to their patients (4,5). Many local and national training programs have been initiated to help develop these skills among primary care physicians, nurses, and non-palliative care specialists (6)(7)(8)(9)(10). A systematic review by Brighton et al in 2017 which evaluated studies of end-of-life care communication skills training, found 153 unique training interventions (11).…”
Section: Introductionmentioning
confidence: 99%